1983
DOI: 10.1136/bmj.286.6370.1015
|View full text |Cite
|
Sign up to set email alerts
|

Change to U-100 insulin does not appear to affect insulin absorption.

Abstract: On 1 March a two year programme began in the United Kingdom of phased transfer of all diabetics requiring insulin to insulin in a strength of 100 units/ml. Factors affecting the absorption of insulin from subcutaneous tissues include site of injection,' exercise,2 dose,3 strength of the insulin, volume, and the patient's age.4 We examined the effect of giving identical doses of soluble insulin in strengths of U-40 (40 units/ml) and U-100 (100 units/ml).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…compared to U-40 when given in a dose of 8 units. In our study as well as in two other studies (Swift, Kennedy and Gerlis 1983;Galloway, Spradlin, Nelson, Wentworth, Davidson and Swarner 1981) no significant differences could be found between identical doses given in different concentrations. Taking all the studies into consideration it seems as if the decreased insulin absorption rate observed with increasing concentration and increasing volume of the injected insulin solution (Binder 1969) is balanced when identical doses of U-40 and of the more concentrated but less voluminous U-100 are given.…”
Section: Discussionsupporting
confidence: 73%
“…compared to U-40 when given in a dose of 8 units. In our study as well as in two other studies (Swift, Kennedy and Gerlis 1983;Galloway, Spradlin, Nelson, Wentworth, Davidson and Swarner 1981) no significant differences could be found between identical doses given in different concentrations. Taking all the studies into consideration it seems as if the decreased insulin absorption rate observed with increasing concentration and increasing volume of the injected insulin solution (Binder 1969) is balanced when identical doses of U-40 and of the more concentrated but less voluminous U-100 are given.…”
Section: Discussionsupporting
confidence: 73%
“…Injection of insulin aspart resulted in a faster onset of action and a shorter duration of action not only compared to U 100-R, which has already been shown previously (Heinemann et al, 1993), but also in comparison to U40-R. It was expected from a previous analysis of various study results that the In some previous studies injection of U40-R resulted in a more rapid increase in serum insulin concentrations compared to U 100-R (Hildebrandt et al, 1983;Heinemann et al, 1992;Hübinger et al, 1992), which could not be confirmed by others (Galloway et al, 1981;Swift et al, 1983;Lauritzen et al, 1984;Chantelau et al, 1985). Measuring the metabolic activity with the glucose clamp technique, all available studies showed comparable results with U40 and UlOO regular insulin (Heinemann et al, 1992;Hübinger et al, 1992; present study).…”
Section: Discussionmentioning
confidence: 91%
“…In earlier studies, the blood glucose profiles for identical doses of U40 or U100 insulins were found to be similar [5,15]. It should be kept in mind that the day-to-day variance of biological effects of subcutaneously injected insulin is at least as high as the mean differences in this study [3,11].…”
Section: Discussionmentioning
confidence: 91%
“…The absorption rate of subcutaneously injected regular insulin has been shown to correlate inversely with the insulin concentration [1,6,9,10]. Recently, differences in the pharmacokinetics of U40 and U100 formulations of regular insulin have been reported [7], but blood glucose profiles for identical doses of U40 and UI00 insulin were similar [5,15]. Since the absorption profiles and glucoselowering potency may vary due to the different volumes necessary for a given dose of insulin, comparative pharmacokinetic trials are needed in order to test whether clinically relevant differences have to be considered when switching diabetic patients from U40 to U100 insulin.…”
Section: Abstract: Insulin Action-insulin Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation